Membangun Masa Depan Remaja Tanpa Pernikahan Dini di RT 19 Karang Indah Kelurahan Sumur Dewa Bengkulu - Fahimah, Iim; Rofiqah, Siti Badria Ainur; Rosana, Gebby; Tahira, Meza; Selvia, Weni (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
This study was conducted by students of KKN MBKM Group 1, Batch IV 2025, at Fatmawati Sukarno State Islamic University of Bengkulu, focusing on the impact of early marriage on adolescents in building greater community awareness. The purpose of this activity is to assess the effectiveness of education and mentoring in reducing the incidence of early marriage and enhancing teenagers' understanding of the social, educational, health, and economic risks associated with marrying at a young age in RT 19 Karang Indah, Sumur Dewa Subdistrict, Bengkulu City. The method used is a participatory approach through counseling sessions, interviews, and group discussions with residents and community leaders. The results show that education about early marriage significantly increases adolescents’ awareness of the importance of education and emotional readiness before entering marriage. Furthermore, this activity also strengthens the role of families and communities in preventing early marriage practices.